Sonochemical synthesis and characterization of Pt/CNT, Pt/TiO2, and Pt/CNT/TiO2 electrocatalysts for methanol electro-oxidation. (20th December 2015) - Bedolla-Valdez, Z.I.; Verde-Gómez, Y.; Valenzuela-Muñiz, A.M.; Gochi-Ponce, Y.; Oropeza-Guzmán, M.T.; Berhault, Gilles; Alonso-Núñez, G.
Highlights: Pt/CNT/TiO2 electrocatalyst was successfully prepared by the sonochemical method. The electrocatalyst Pt/CNT/TiO2 was synthesized without heat treatments, additives or surfactants. The TiO2 -Pt interaction improves the CO-tolerance of Pt/CNT/TiO2, as well as the electrocatalyst stability. Low amount of multi-walled carbon nanotubes increases the current density of Pt/CNT/TiO2 significantly compared to Pt/TiO2 . Abstract: Pt electrocatalyst supported on composite formed of multi-walled carbon nanotubes and titanium oxide (CNT/TiO2 ) was successfully synthesized by a sonochemical method without heat treatments, surfactants or additives. This electrocatalyst could be used for direct methanol fuel cells (DMFC) applications. For comparison, Pt/CNT and Pt/TiO2 electrocatalysts were prepared as reference samples. Structural properties and morphology of the synthesized materials were examined by X-ray diffraction, transmission electron microscopy, Raman spectroscopy, X-ray photoelectron spectroscopy and their specific surface areas were determined by the Brunauer-Emmett-Teller method. The Pt and acid-treated CNT contents were analyzed by inductively coupled plasma atomic emission spectroscopy and thermogravimetric analysis, respectively. The electrochemical properties of the synthesized electrocatalysts were evaluated by cyclic voltammetry (CV) and chronoamperometry in a three-electrode cell at room temperature. The evaluation performed using electrochemical techniques suggests that TiO2 promotes the CO-tolerance due to TiO2 -Pt interaction. The CV tests demonstrated that 6 wt.% of acid-treated CNT increases significantly the current density when Pt selectively interacts with TiO2 .